1987
DOI: 10.3382/ps.0660834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eggshell Cuticle Removal and Incubation Humidity on Embryonic Development and Hatchability of Broilers

Abstract: The effects of eggshell cuticle removal and two levels of incubation humidity 28.3 C [50% relative humidity (RH)] and 30.0 C (55% RH) wetbulb temperature (WB) on embryonic mortality and hatchability were determined from broiler hatching eggs laid during 38, 42, 48, and 54 weeks of age. Variables measured were: egg weight loss during the first 17 days of incubation, hatch at Days 19.5 and 20.5 of incubation, hatch of fertile eggs, stage of embryonic mortality, and chick weight at 21.5 days of incubation. Day 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 35 publications
3
17
0
2
Order By: Relevance
“…As can be seen from this table that largest body weights were observed for chicks either at hatch or at pull out for propolis 14% and these results could be related with the results of decreasing egg weight loss during incubation as presented in Table 2. These results are confirmed with those reported by Peebles et al (1987) who showed that chick weight was reduced by increasing incubation egg weight loss from zero to 18 days. Also, Davis et al (1988) reported that low or excess water are incorporated into new tissues so affecting chick weight.…”
Section: Resultssupporting
confidence: 83%
“…As can be seen from this table that largest body weights were observed for chicks either at hatch or at pull out for propolis 14% and these results could be related with the results of decreasing egg weight loss during incubation as presented in Table 2. These results are confirmed with those reported by Peebles et al (1987) who showed that chick weight was reduced by increasing incubation egg weight loss from zero to 18 days. Also, Davis et al (1988) reported that low or excess water are incorporated into new tissues so affecting chick weight.…”
Section: Resultssupporting
confidence: 83%
“…By contrast, this effect may be detrimental to hatchability in older flocks where excessive water loss may be a problem (Vick and Brake, 1986). Increased incubational humidity would be appropriate in order to balance the effect (Peebles et al, 1987).…”
Section: Experiments 5 Tomentioning
confidence: 99%
“…When present, its thickness and chemical composition can vary across taxa, and may contain proteins, polysaccharides, lipids, calcium carbonate and calcium phosphates [29][30][31][32][33]. Although the cuticle's roles in embryonic development and antimicrobial defence of eggshells are well studied [32,[34][35][36], its role in modulating the visual appearance of eggshells is poorly understood [37][38][39]. The chemical composition and structure of the cuticle can differ from the true eggshell underneath [33], and therefore may interact with light differently.…”
Section: Introductionmentioning
confidence: 99%